Employees Perceptions about Corporate Social Responsibility—Understanding CSR and Job Engagement through Meaningfulness, Bottom-Up Approach and Calling Orientation - Cunha, Sara (2022)
This article analyses the effect of employees’ perceptions of corporate social responsibility (CSR) on job engagement, and we measure meaningfulness experienced and the role of cross-level sensemaking factors, such as the bottom-up approach and calling orientation. Drawing on qualitative data, collected among workers that had CSR implemented in their companies, our findings suggest that both calling orientation and meaningfulness influence the positive impact of the CSR perceptions on job engagement through sequential mediation. The calling orientation has an important role in this relationship because meaningfulness alone does not influence the relationship between CSR and job engagement. Additionally, employees’ perceptions of CSR positively influence job engagement. Furthermore, our research indicates that the meaningfulness experienced by workers increases in the presence of a bottom-up approach in what concerns the definition and implementation of CSR actions of the company. Overall, this research expands our understanding of how people find meaningfulness through individual experiences of CSR.